The Rise of Women in the Poems A Woman's Place by Frohman (2018), Remember, Woman by Leyva (2015), and A Woman's Place by Chidi (2005) - Gernanda Che Guevara; Desvalini Anwar (English Language and Literature, 2022)
This research is an analysis of three poems by Denice Frohman entitled A Woman's Place (2018), by Reese Leyva entitled Remember, Woman (2015), and by Sylvia Chidi entitled A Woman's Place (2005). This analysis explores the struggles of women in conveying their rights and positions, obtaining gender equality and breaking the patriarchal culture. The analysis of the three poems also reveals the extent to which the author implies the woman’s effort to gain equality. The study of these poems is analyzed with feminist theory and supported with the theories of gender inequality and gender oppression. The results of this study indicate that women already have awareness about their situation and determined to change it. This research will include; 1) injustices and oppression towards women, 2) women’s awareness, 3) women efforts to achieve equality.